Clinical trials in Charcot-Marie-Tooth disorders: a retrospective and preclinical assessment - Nair, Malavika A.; Niu, Zhiyv; Madigan, Nicholas N.; Shin, Alexander Y.; Brault, Jeffrey S.; Staff, Nathan P.; Klein, Christopher J. (Frontiers in Neurology, 2023)
Objective This study aimed to evaluate the progression of clinical and preclinical trials in Charcot-Marie-Tooth (CMT) disorders. Background CMT has historically been managed symptomatically and with genetic counseling. The evolution of molecular and pathologic understanding holds a therapeutic promise in gene-targeted therapies. Methods ClinicalTrials.gov from December 1999 to June 2022 was data extracted for CMT with preclinical animal gene therapy trials also reviewed by PubMed search. Results The number of active trials was 1 in 1999 and 286 in 2022. Academic settings accounted for 91% and pharmaceutical companies 9%. Of the pharmaceutical and academic trials, 38% and 28%, respectively, were controlled, randomized, and double-blinded. Thirty-two countries participated: the United States accounted for 26% (75/286). In total, 86% of the trials were classified as therapeutic: 50% procedural (21% wrist/elbow surgery; 22% shock wave and hydrodissection therapy), 23% investigational drugs, 15% devices, and 11% physical therapy. Sixty-seven therapeutic trials (49%) were designated phases 1–2 and 51% phases 3–4. The remaining 14% represent non-therapeutic trials: diagnostic testing (3%), functional outcomes (4%), natural history (4%), and standard of care (3%). One-hundred and three (36%) resulted in publications. Phase I human pharmaceutical trials are focusing on the safety of small molecule therapies (n = 8) and AAV and non-viral gene therapy (n = 3). Preclinical animal gene therapy studies include 11 different CMT forms including viral, CRISPR-Cas9, and nanoparticle delivery. Conclusion Current CMT trials are exploring procedural and molecular therapeutic options with substantial participation of the pharmaceutical industry worldwide. Emerging drug therapies directed at molecular pathogenesis are being advanced in human clinical trials; however, the majority remain within animal investigations.